Determinants of E-Payment Services, Financial and Macroeconomic Ratios to Company Performance - S, Lulu Ilmang; Nawirah, Nawirah (EQUITY, 2020)
The level of achievement of an organization can be seen from the company's performance. Performance shows the ability of management in managing a company. Performance appraisal can be seen from various internal and external factors. The purpose of this research is to determine the effect of partial and simultan digital service systems based on digital e-payment, financial ratios, macroeconomics on company performance. This research type is quantitative method with descriptive approach. The data is secondary data and this research use multiple linear regression analysis method. The population is banking companies listed on the Indonesia Stock Exchange (BEI) within year of 2016-2018. Sampling method used purposive sampling so obtained 33 samples. The results of this research with determination coefficient at 6.22% simultaneously digital-based e-payment service systems, financial ratios, macroeconomics have a significant influence to company performance. Partially, digital e-payment based services and financial ratios (NPL, NIM) have a significant positive influence to company performance.